(3QSGdI aj GdcdGe GdfaSjs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI hGdJUdjI hHYO ; CjgG GdGHf GdcQje habfj Gddg hEjGc (B: (3Efc SCdJ efj QSGdI CNJUQ dc ajgG RHOI eG ddCFeI GdCYdGe aj eOdhd GdfXe GdeYLR (B() (3gd gh GdcdGe GdfaSj GdbGFe HGdPGJ GdYGdjI Ch eOdhdg eOdhd GdcdGe GdfaSj GdbOje dG Yjfgs
(3BNQgG (B:s
(3hPdc dCfg GdgGOj Edi eG ajg ceGd GdYHGO hGdOGYj Edi eG Hg jfJXe UdGM GdeYGT hGdeYGO hde jLYd dg TjFG ef GdYhL HGNJdGd aj GddaX (B( ) (3aj GdeYfis
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds